APPLICATION OF THE LARAVEL FRAMEWORK IN THE DEVELOPMENT OF A WEB-BASED INFORMATION SYSTEM FOR BIOPHYSIO PHYSIOTHERAPY CLINIC - Terlia, Carisna; Firdonsyah, Arizona (Antivirus : Jurnal Ilmiah Teknik Informatika, 2024)
Healthcare services particularly in the field of physiotherapy, play a crucial role in the recovery of patients with movement and functional impairments. The Biophysio Physiotherapy Clinic faces challenges in managing patient data, scheduling therapy sessions, and tracking patient progress as the number of patients increases. To address these issues, this study developed a web-based information system using the Laravel Framework, known for its flexibility. The Rapid Application Development (RAD) method was employed in the development of this system, involving iterative user feedback. The testing results demonstrate excellent system performance in terms of speed and responsiveness, with a 95% score on Google PageSpeed Insights, and effective handling of workload as evidenced by load testing results. In the load testing, the average response time for login requests was 6483 ms, while for admin requests, it was 1803 ms. The throughput reached 0.06 requests per second for login requests and 1.42 requests per second for admin requests. With stable response times and no errors during testing, this system is ready for implementation and is expected to improve the operational efficiency of the clinic while providing a better user experience. The Biophysio Physiotherapy Clinic’s Web-Based Information System successfully passed both performance testing and load testing